Diet and risk of glioma: combined analysis of 3 large prospective studies in the UK and USA. Issue 7 (23rd January 2019) - Kuan, Ai Seon; Green, Jane; Kitahara, Cari M; De González, Amy Berrington; Key, Tim; K. Reeves, Gillian; Floud, Sarah; Balkwill, Angela; Bradbury, Kathryn; Liao, Linda M; Freedman, Neal D; Beral, Valerie; et al.
Abstract: Background: Available evidence on diet and glioma risk comes mainly from studies with retrospective collection of dietary data. To minimize possible differential dietary recall between those with and without glioma, we present findings from 3 large prospective studies. Methods: Participants included 692 176 from the UK Million Women Study, 470 780 from the US National Institutes of Health–AARP study, and 99 148 from the US Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial. Cox regression yielded study-specific adjusted relative risks for glioma in relation to 15 food groups, 14 nutrients, and 3 dietary patterns, which were combined, weighted by inverse variances of the relative risks. Separate analyses by <5 and ≥5 years follow-up assessed potential biases related to changes of diet before glioma diagnosis. Results: The 1 262 104 participants (mean age, 60.6 y [SD 5.5] at baseline) were followed for 15.4 million person-years (mean 12.2 y/participant), during which 2313 incident gliomas occurred, at mean age 68.2 (SD 6.4). Overall, there was weak evidence for increased glioma risks associated with increasing intakes of total fruit, citrus fruit, and fiber and healthy dietary patterns, but these associations were generally null after excluding the first 5 years of follow-up. There was little evidence for heterogeneity of results by study or by sex. Conclusions: The largest prospective evidence to date suggests little, if any, association between major food groups, nutrients, or common healthy dietary patterns and glioma incidence. With the statistical power of this study and the comprehensive nature of the investigation here, it seems unlikely we have overlooked major effects of diet on risk of glioma that would be of public health concern.